The importance of nursing work in the prevention and treatment of pressure injuries: A literature review (Research, Society and Development, 2025)
Pressure injuries (PI) represent a major challenge in hospital care, especially for patients with reduced mobility. These injuries cause serious complications, prolonged hospitalizations, and increased healthcare costs. This study aimed to analyze best nursing practices in the prevention and treatment of PI. This is an integrative review conducted in LILACS and SciELO databases, covering studies published between 2021 and 2025. After screening 229 articles, 20 were selected. Results highlighted the relevance of the Braden Scale, frequent repositioning, special mattresses, and Nursing Care Systematization (NCS). It is concluded that continuous professional training is crucial for reducing the incidence of PI.